Reversible splenial lesion syndrome in children: clinical analysis and summary of a case series. Issue 4 (April 2020) - Zhang, Xinying; Chen, Na; Guo, Jiamin; Li, Shuwei; Xu, Jiaming; Zhu, Weiwei; Ma, Aihua
Objective: To describe clinicoradiological features and outcomes of reversible splenial lesion syndrome (RESLES) in children. Methods: Data from 23 children (25 RESLES episodes; two patients had recurring episodes) was retrospectively reviewed at the Department of Pediatric Neurology, Shandong Provincial Hospital Affiliated with Shandong University, China. Primary disease, central nervous system manifestations, treatments, outcomes, and laboratory examination, electroencephalogram, and magnetic resonance imaging (MRI) results were assessed. Results: Fourteen boys and nine girls (23 patients; 8 months to 11 years old) with 25 RESLES episodes (20 type-1, 5 type-2) were enrolled. Epileptic seizure and infection were the most common pathogenesis. Prominent clinical manifestations were disturbance of consciousness and visual disturbance. Cranial MRI of 20 RESLES type-1 episodes showed oval lesions in the splenium of corpus callosum (SCC), and five RESLES type-2 episodes showed lesions in the entire corpus callosum that were associated with the symmetric cerebral white matter. Lesions were hyperintense on diffusion-weighed images (DWI) and disappeared when later reviewed (range, 4–30 days). Conclusions: RESLES etiology in children is complex, and its clinical manifestations are nonspecific. Diagnosis mainly depends on cranial MRI, especially DWI, showing highly intense lesions on SCC. RESLES has a good prognosis and excessive treatment should be avoided.